RUMUSAN PENGATURAN CREDIT CARD FRAUD DALAM HUKUM PIDANA INDONESIA DITINJAU DARI ASAS LEGALITAS - Said Noor Prasetyo (Faculty of Law, University of Muhammadiyah Malang, 2016)
Internet is an information technology development product. Internet provide so many benefits for society in various field of life. One of its benefit is electronic payment system in e-commerce system. That benefits are also used by irresponsible persons for te crimes. One form ofcrimes in these field was credit card fraud. Based on data, Indonesia is a country with te highest rate of credit card fraud around the world. This is caused by the weakness of legal substance that regulate such crime. The Purpose of this research is to looking for such weakness based on principles of legality point of view. For such purpose, researcher use normative juridical of research methods with the konseptual and statute approach.